HUBUNGAN PERSEPSI BEBAN KERJA DAN DISIPLIN KERJA DENGAN KINERJA PEGAWAI SELAMA MASA PANDEMI COVID-19 DI PUSKESMAS II DENPASAR SELATAN - Putri, Putu Anindya Eka; Listyowati, Rina (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 3 (2021): Desember 2021, 2022)
ABSTRACT Puskesmas is the front line during the pandemic in carrying out case tracking, monitoring of OTG, COVID-19 suspects. With the addition of these activities, it can have an impact on employee performance during the pandemic. In improving their performance, there are several factors that need to be considered, namely workload and work discipline. The purpose of this study was to determine the perception of workload and work discipline with employee performance at Puskesmas II Denpasar Selatan. Quantitative research design with a cross sectional approach. The research sample was all employees at Puskesmas II Denpasar Selatan namely 71 respondents, the sampling technique used the total sampling method. Univariate results show the characteristics of employees at Puskesmas II Denpasar Selatan, amounting to 26-35 years (43.66%), female (71.83%), with bachelor degree (47.89%), working status PNS (54.93%) with work experience >10 years (56.34%) Bivariate results show that there is no relationship between workload and employee performance (p=0.56), there is a relationship between work discipline and employee performance (p=0.04). Improvement of the work system schedule and management of working time during the pandemic, monitoring the discipline of puskesmas employees and providing rewards for employees who have worked in accordance with the principles of the agency. Key words: Perception of Workload, Work Discipline, Employee Performance